A softened membrane model for prestressed concrete composite box girders with corrugated steel webs under pure torsion. Issue 2 (January 2019) - Shen, Kongjian; Wan, Shui; Mo, YL; Li, Xiayuan
Torsion can be regarded as a principal factor in some cases, such as in curved girders and eccentrically loaded girders, when conducting the structural analysis of prestressed concrete composite box girders with corrugated steel webs. Recently, a rational model, called the softened membrane model for torsion, was proposed for the torsional analysis of reinforced concrete members; thereafter, this model was extended to prestressed concrete members under pure torsion and called softened membrane model for torsion prestressed concrete. This article presents a modified model, the softened membrane model for torsion prestressed concrete for prestressed concrete composite box girders with corrugated steel webs, to analyze full torsional behavior. To build the model, the softened membrane model for torsion in reinforced concrete members is first extended to perform the torsional analysis of prestressed concrete composite box girders with corrugated steel webs by incorporating the torsional contribution of corrugated steel webs. Afterward, the initial stresses and strains due to prestressing are considered to extend the softened membrane model for torsion to softened membrane model for torsion prestressed concrete for prestressed concrete composite box girders with corrugated steel webs by modifying the equilibrium equations, convergence criteria, and constitutive laws of materials. The modified model is validated by experimental data and is proven to be capable of predicting the overall torque–twist curve, especially the precracked branch and postcracked ascending branch. In addition, a comparison between the softened membrane model for torsion and softened membrane model for torsion prestressed concrete indicates that the torque values before and after concrete cracking will be overestimated and underestimated, respectively, without considering the effect of the initial stresses and strains. Finally, another comparison shows that the softened membrane model for torsion prestressed concrete is superior to the rotating-angle truss model for torsion in its ability to predict the precracked branch of the torque–twist curve.